A COMPARATIVE STUDY OF STANDARD IPOM AND IPOM PLUS IN LAPAROSCOPIC MANAGEMENT OF INCISIONAL HERNIAS - Kumar, Abhay; Kumar, Om Prakash; Bhushan, Vibhuti (Student’s Journal of Health Research Africa, 2024)
Background: Incisional hernias present significant challenges post-abdominal surgeries, with complications such as seroma formation and hernia recurrence being common. This study evaluates the efficacy of Intraperitoneal Onlay Mesh (IPOM) and IPOM PLUS (closure of the hernia defect with mesh placement) techniques in managing these hernias. Methods: A randomized clinical trial was conducted on 60 patients at IGIMS, Patna, comparing the outcomes of the IPOM and IPOM PLUS techniques. The primary outcomes measured were operation time, seroma formation, mesh bulging, mesh eventration, recurrence, and postoperative complications. Results: The IPOM PLUS technique resulted in significantly reduced seroma formation (10% vs. 30%) and a lower recurrence rate compared to the standard IPOM method. Operation times were longer for IPOM PLUS, but without a significant increase in other complications. Conclusion: IPOM PLUS appears to offer a substantial improvement over standard IPOM in reducing the incidence of seroma and possibly recurrence rates. Further studies with larger sample sizes and longer follow-up are required to validate these findings and determine the long-term benefits and cost-effectiveness of the IPOM PLUS technique.